Enhancement of alkaloid production in opium and California poppy by transactivation using heterologous regulatory factors - Apuya, N.R.; Park, J.H.; Zhang, L.; Ahyow, M.; Davidow, P.; Van Fleet, J.; Rarang, J.C.; Rarang, J.C.; Johnson, T.J.; Yoo, H.D.; Trieu, A.; Krueger, S.; et al.
Genes encoding regulatory factors isolated from Arabidopsis , soybean and corn have been screened to identify those that modulate the expression of genes encoding for enzymes involved in the biosynthesis of morphinan alkaloids in opium poppy ( Papaver somniferum ) and benzophenanthridine alkaloids in California poppy ( Eschscholzia californica ). In opium poppy, the over-expression of selected regulatory factors increased the levels of PsCOR (codeinone reductase), Ps4 _O OMT ( S -adenosyl- L -methionine:3 _O -hydroxy- N -methylcoclaurine 4_O O ltransferase)and Ps6OMT [( R , S )-norcoclaurine 6- O -methyltransferase]transcripts by 10- to more than 100-fold. These transcriptional activations translated into an enhancement of alkaloid production in opium poppy of up to at least 10-fold. In California poppy, the transactivation effect of regulatory factor WRKY1 resulted in an increase of up to 60-fold in the level of EcCYP80B1 [( S )- N -methylcoclaurine 3 _O -hydroxylase]and EcBBE (berberine bridge enzyme)transcripts. As a result, the accumulations of selected alkaloid intermediates were enhanced up to 30-fold. The transactivation effects of other regulatory factors led to the accumulation of the same intermediates. These regulatory factors also led to the production of new alkaloids in California poppy callus culture.
Keywords: CALIFORNIA POPPY; MORPHINAN ALKALOIDS; MORPHINE; OPIUM POPPY; THEBAINE; TRANSCRIPTION FACTORS